BATAS KEKUASAAN PRESIDEN DALAM KONSTITUSI INDONESIA: Limits Of The President's Powers In The Indonesian Constitution - Mohammad Haris Taufiqur Rahman (UIN Kiai Haji Ahmad Sidiq Jember, 2024)
The presidential system of government adopted by Indonesia ideally provides broad powers for the president to carry out his executive duties. These broad powers can only be limited by other powers for constitutional reasons. This article intends to explore two major concepts in constitutional law, namely prerogative rights and the principle of separation of powers as constitutional limits on the president's executive power. The analytical tools used include historical approaches, constitutional theory and practices applicable in other countries, namely the United States, New Zealand and Canada. The results of the analysis show that prerogative rights are different from the president's executive rights. Prerogative rights provide broad space for the president to use his powers to fill spaces that have not been regulated in the constitution while carrying out his executive duties. The limitation of prerogative rights is that their use is limited to emergencies until the legislative body can regulate it in legislation. Meanwhile, the principle of separation of powers postulates two interpretations, namely formalist and functionalist. The formalist view is based on the unitary power doctrine which prohibits all forms of intervention by other branches of power on executive power, while the functionalist approach assumes that limits on executive power are possible as long as they do not have a fundamental impact on the president's ability to exercise his executive power. Abstrak Sistem pemerintahan presidensial yang dianut oleh Indonesia idealnya memberikan kekuasaan yang luas bagi presiden untuk melaksakan tugas eksekutifnya. Kekuasaan yang luas tersebut hanya dapat dibatasi oleh kekuasaan lain dengan alasan konstitusional. Tulisan ini bermaksud untuk mendalami dua konsep besar dalam hukum tata negara yaitu hak prerogatif dan prinsip separation of powers sebagai batasan konstitusional kekuasaan eksekutif presiden. Alat analisis yang digunakan antara lain adalah pendekatan sejarah, teori konstitusi dan praktek yang berlaku dinegara lain yaitu Amerika Serikat, New Zealand dan Canada. Hasil analisis menunjukkan bahwa hak prerogatif berbeda dengan hak eksekutif presiden. Hak prerogatif memberikan ruang yang luas kepada presiden untuk menggunakan kekuasaannya untuk mengisi ruang yang belum diatur dalam konstitusi sepanjang untuk menjalankan tugas eksekutifnya. Batasan hak prerogatif adalah penggunaannya yang dibatasi pada keadaan darurat sampai dengan lembaga legislatif dapat mengaturnya dalam perundangundangan. Sedangkan prinsip separation of powers mendalilkan dua penafsiran yaitu formalis dan fungsionalis. Pandangan formalis mendasarkan dirinya pada unitary power doctrine yang melarang segala bentuk intervensi cabang kekuasaan lain terhadap kekuasaan eksekutif, sedangkan pendekatan fungsionalis beranggapan bahwa batasan kekuasaan eksekutif dimungkinkan selama tidak berdampak secara mendasar kepada presiden untuk menjalankan kekuasaan eksekutifnya.